Relationship between the number of hospital pharmacists and hospital pharmaceutical expenditure: a macro-level panel data model of fixed effects with individual and time - Ming Wei; Xuemei Wang; Dandan Zhang; Xinping Zhang (BMC, 2020)
Abstract Background The rapid increase in pharmaceutical expenditure (PE) has been a main problem of global healthcare reform for decades. Previous studies demonstrated that pharmacists play an indispensable role in controlling PE, but macro-research evidence is scarce. Exploring the role of pharmacists from a macro-perspective is essential for pharmacy source allocation with an advantage of extensive applicability over regions. This study aimed to explore the relationship between the number of hospital pharmacists and hospital PE and to provide a macro-perspective evidence to curb the increasing PE and decline unnecessary medications. Methods Data were extracted from China Health Statistics Yearbook from 2011 to 2018. A panel dataset with 31 provinces from 2010 to 2017 was constructed. Amongst them, 'Number of hospital pharmacists per 1 million of population' (HLPT) was selected as an independent variable, 'Per visit of hospital outpatient pharmaceutical expenditure' (OTPE) and 'Per capita of hospital inpatient pharmaceutical expenditure' (ITPE) were selected as dependent variables, and 'Number of hospital physicians per 1 million of population' (HLPN) and 'Drug price index' (DPI) were applied as control variables. Fixed-effect panel data analysis was performed to evaluate the relationship between the number of hospital pharmacists and hospital PE. Results HLPT had a significant and negative relationships with OTPE (β1 = − 0.0893, p = 0.0132) and ITPE (β1 = − 4.924, p < 0.001). Considering the control variables, the significant and negative relationships with HLPT and OTPE remained unchanged (β1 = − 0.141, p < 0.001; β1 = − 4.771, p < 0.001, respectively), indicating that an increase in hospital pharmacist per 1 million of population led to a decrease of ¥474 million ($67.4 million) OTPE and ¥902 million ($128 million) ITPE in 2017. Overall, in 2017, an increase of 1 hospital pharmacist led to a decrease of approximately ¥1 million ($142 thousands) hospital PE nationwide. Conclusion This study confirmed the negative relationship between hospital pharmacists and hospital PE, indicating that hospital pharmacists might play a significant role in controlling PE. Pharmacists were encouraged to participate in more drug-therapy-related activities, such as medication reconciliation.